(4-Hydroxy-2-oxidobenzaldehyde thiosemicarbazonato-kappa O-3(2),N-1,S)(1, 10-phenanthroline-kappa N-2,N ')zinc(II) dimethyl sulfoxide disolvate monohydrate - Tan, Kong Wai; Ng, S.W.; Maah, Mohd Jamil; Ng, C.H. (International Union of Crystallography, 2009)
The Zn-II atom in the title compound, [Zn(C8H7N3O2S)-(C12H8N2)]center dot 2C(2)H(6)OS center dot H2O, is N,N '-chelated by the N-heterocycle and N, O, S-chelated by the deprotonated Schiff base in a distorted square-pyramidal enviroment. Hydrogen bonds link the mononuclear molecule, the water and the dimethyl sulfoxide (DMSO) molecules into a linear chain motif. One DMSO molecule is disordered over two positions in respect of the S atom in an approximate 1:1 ratio.